2021
DOI: 10.1242/jcs.256792
|View full text |Cite
|
Sign up to set email alerts
|

WNT-responsive SUMOylation of ZIC5 promotes murine neural crest cell development, having multiple effects on transcription

Abstract: Zinc finger of the cerebellum (Zic) proteins act as classical transcription factors to promote transcription of the Foxd3 gene during neural crest cell specification. Additionally, they can act as co-factors that bind TCF molecules to repress WNT/β-catenin-dependent transcription without contacting DNA. Here, we show ZIC activity at the neural plate border is influenced by WNT-dependent SUMOylation. In a high WNT environment, a lysine within the highly conserved ZF-NC domain of ZIC5 is SUMOylated, which decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 67 publications
(97 reference statements)
1
31
0
Order By: Relevance
“…During murine NCC formation, ZIC5 regulation of Foxd3 expression requires post-translational modification of the ZIC5 protein by SUMOylation at a lysine within the highly conserved ZF-NC domain [ 25 ]. The paralogous ZIC3 lysine is also a SUMO substrate [ 49 ], and a high-throughput proteomic study [ 50 ] and search for high-probability consensus SUMOylation motifs within the ZIC proteins [ 25 , 51 ] suggest all human ZIC proteins can be SUMOylated. To determine if this is the case, the various ZICs were assessed using the UBC9 fusion-directed SUMOylation (UFDS) system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During murine NCC formation, ZIC5 regulation of Foxd3 expression requires post-translational modification of the ZIC5 protein by SUMOylation at a lysine within the highly conserved ZF-NC domain [ 25 ]. The paralogous ZIC3 lysine is also a SUMO substrate [ 49 ], and a high-throughput proteomic study [ 50 ] and search for high-probability consensus SUMOylation motifs within the ZIC proteins [ 25 , 51 ] suggest all human ZIC proteins can be SUMOylated. To determine if this is the case, the various ZICs were assessed using the UBC9 fusion-directed SUMOylation (UFDS) system.…”
Section: Resultsmentioning
confidence: 99%
“…SUMOylation generally modifies a lysine within a motif of conserved residues (ΨKXE), enabling the identification of high-probability SUMO sites via sequence analysis. In addition to the highly conserved SUMOylation site in the ZF-NC domain within ZIC1-4, our previous analysis showed that human ZIC1 and ZIC3 also contain a second high-probability canonical SUMOylation site at the boundary of zinc fingers 3 and 4 [ 25 ] ( Figure 1 a). To determine which of the predicted SUMOylation sites within ZIC1-4 are bona fide sites of SUMO attachment in HEK293T cells, each putative, modified lysine (K) was converted to an arginine (R) (which cannot be modified be SUMOylation) in the V5 epitope-tagged mammalian expression construct.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations